Mechanical properties of geopolymer concrete containing polyvinyl alcohol fiber exposed to high temperature - Tanyildizi, Harun; Yonar, Yavuz (Elsevier Sci Ltd, 2016)
The objective of the study is to scrutinize the high-temperature resistance of geopolymer concrete with polyvinyl alcohol fiber (PVA). F-class fly ash was used for the production of geopolymer. Polyvinyl alcohol fiber was used in 0%, 1%, and 2% by mass of the fly ash. Sodium silicate solution and sodium hydroxide were used as alkali activators. 100 x 100 x 100 mm cube and 75 x 75 x 300 mm beam samples were produced using the geopolymer concrete. The all mix was produced by curing these samples at 60, 80, and 100 degrees C. Then the samples were air-cured for 28 days at 20 +/- 2 degrees C. At the end of the curing period, the samples were exposed to high temperatures at 20 degrees C, 400 degrees C, 600 degrees C and 800 degrees C. Compressive strength and flexural strength tests were conducted on the samples. The findings demonstrated that as the PVA fiber ratio increased, compressive strength and flexural strength of the geopolymer concrete increased. Furthermore, compressive strength and flexural strength of the samples that were exposed to high temperatures demonstrated reductions which samples. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Geopolymer concrete; Polyvinyl alcohol fiber; High temperature; Mechanical properties